Comprehensive Physiology 2018
DOI: 10.1002/cphy.c170027
|View full text |Cite
|
Sign up to set email alerts
|

SLC9 Gene Family: Function, Expression, and Regulation

Abstract: The Slc9 family of Na /H exchangers (NHEs) plays a critical role in electroneutral exchange of Na and H in the mammalian intestine as well as other absorptive and secretory epithelia of digestive organs. These transport proteins contribute to the transepithelial Na and water absorption, intracellular pH and cellular volume regulation as well as the electrolyte, acid-base, and fluid volume homeostasis at the systemic level. They also influence the function of other membrane transport mechanisms, affect cellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 338 publications
(532 reference statements)
0
48
0
Order By: Relevance
“…SLC9A1 is expressed in almost every tissue in the body, although the transporter is often localized to specialized membrane domains in tissues [297,298]. Other SLC9 transporters are expressed in a more tissue or temporally dependent manner, like SLC9A4, which is expressed primarily in the stomach [292]. Cellular localization of these proteins varies greatly within the family as well, with SLC9A1, SLC9A2, and SLC9A4 (NHE4) all localizing to the plasma membrane of cells [289].…”
Section: Slc9mentioning
confidence: 99%
“…SLC9A1 is expressed in almost every tissue in the body, although the transporter is often localized to specialized membrane domains in tissues [297,298]. Other SLC9 transporters are expressed in a more tissue or temporally dependent manner, like SLC9A4, which is expressed primarily in the stomach [292]. Cellular localization of these proteins varies greatly within the family as well, with SLC9A1, SLC9A2, and SLC9A4 (NHE4) all localizing to the plasma membrane of cells [289].…”
Section: Slc9mentioning
confidence: 99%
“…Studies have shown that aquaporins (AQPs) [17][18][19] and Na+/H+ exchangers (NHEs) [20][21][22][23][24] are critical for the absorptive and secretory function of the gastric epithelia. In addition, serum levels of acute phase proteins (APPs) [25,26] are correlated with the severity of diarrhea and intestinal inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Two further zinc transporters, Slc39a2 and Slc39a11, were enriched in lung macrophages (Cluster 10). This lung macrophage-enriched cluster also contains Slc52a3, encoding a riboflavin transporter, Slc6a4 (sodium and chloride dependent sodium symporter) and 2 members of the Slc9 family of sodium-hydrogen exchange (NHE) transporters (Slc9a4 and Slc9a7) which are more traditionally associated with epithelial function [149].…”
Section: Expression Of Solute Carriers and Metabolism Genes In Macropmentioning
confidence: 99%